The “Projection-by-Projection” (PbP) criterion for multiaxial random fatigue loadings: Guidelines to practical implementation (Fracture and Structural Integrity, 2018)
This work is motivated by the increasing interest towards the application of the “Projection-by-Projection” (PbP) spectral method in finite element (FE) analysis of components under multiaxial random loadings. To help users and engineers in developing their software routines, this paper presents a set of numerical case studies to be used as a guideline to implement the PbP method. The sequence of analysis steps in the method are first summarized and explained. A first numerical example is then illustrated, in which various types of biaxial random stress are applied to three materials with different tension/torsion fatigue properties. Results of each analysis step are displayed explicitly to allow a plain understanding of how the PbP method works. The examples are chosen with the purpose to show the capability of the method to take into account the effect of correlation degree among stress components, and the relationship between material and multiaxial stress in relation to the tension/torsion fatigue properties. A case study is finally discussed, in which the method is applied to a FE structural durability analysis of a simple structure subjected to random excitations. The example describes the flowchart and the program by which to implement the method through Ansys APDL software. This final example illustrates how the PbP method is an efficient tool to analyze multiaxial random stresses in complex structures.
Keywords: Multiaxial fatigue; Random stress; Frequency-domain approach; Power Spectral Density (PSD); Finite element method